Association between sugar cane burning and acute respiratory illness on the island of Maui. Issue 1 (December 2015) - Mnatzaganian, Christina; Pellegrin, Karen; Miyamura, Jill; Valencia, Diana; Pang, Lorrin
Abstract Background Sugar cane harvesting by burning on Maui island is an environmental health issue due to respiratory effects of smoke. Volcanic smog ("vog") from an active volcano on a neighboring island periodically blankets Maui and could confound a study of cane smoke's effects since cane burning is not allowed on vog days. This study examines the association between cane burning and emergency department (ED) visits, hospital admissions, and prescription fills for acute respiratory illnesses. Methods This retrospective study controlled for confounders that could increase respiratory distress on non-burn days by matching each burn day with a non-burn day and then comparing the ratio of patients with respiratory distress residing in the path of sugar burn smoke to those residing elsewhere on Maui on burn versus non-burn days. Patients with acute respiratory distress were defined as those with one or more acute respiratory diagnoses at one of the hospitals or emergency departments on Maui. Separately, patients with acute respiratory illness were identified through prescription records from four community pharmacies, specifically defined as those who filled prescriptions for acute respiratory distress. Results There were 1, 256 reports of respiratory distress prescriptions and 686 hospital/ED diagnoses of acute respiratory illness. The ratio of cases within to outside of smoke exposure was higher on burn days for both the ED/hospital data and the pharmacy, though not statistically significant. In post-hoc analyses of the pharmacy data based on the number of acres burned as a proxy for volume of smoke, there was a dose response trend for acreage burned such that the highest quartile showed a statistically significant higher proportion of acute respiratory distress in the exposed versus non-exposed regions (P = 0.015, OR 2.4, 95 % CI [1.2–4.8]). Conclusions After adjusting for confounders on non-burn days, there was a significantly higher incidence of respiratory distress in smoke-exposed regions when greater amounts of acres were burned. Health officials should consider actions to reduce the negative health outcomes associated with sugar cane burning practices.